Utility of the neonatal and pediatric sequential organ failure assessment scores in critically ill term neonates - Nicolas, Lara; Wynn, James L.; de la Cruz, Diomel (Frontiers in Pediatrics, 2025)
BackgroundThe pediatric sequential organ failure assessment (pSOFA) and neonatal SOFA (nSOFA) scores are used to assess organ dysfunction and predict mortality in critically ill children and neonates. However, their utility in predicting mortality in term neonates admitted to pediatric ICU/pediatric cardiac ICU (PICU/PCICU) and neonatal ICU (NICU) remains unknown.MethodsWe conducted a single-center retrospective cohort study of electronic health records of 4,403 and 379 term neonates admitted to NICU and PICU/PCICU, respectively. Hourly pSOFA and nSOFA scores were calculated. The primary outcome was in-hospital mortality. The area under the receiving operating characteristic curve (AUROC) for mortality was calculated.ResultsBoth scores predicted mortality in both settings (AUROC range, 0.79–0.95). The pSOFA showed a larger difference between survivors and non-survivors in the PICU/PCICU cohort, while nSOFA captured critical mortality risk factors in neonates across both settings.ConclusionsBoth pSOFA and nSOFA predicted mortality with good to very good discrimination in critically ill term neonates admitted to PICU/PCICU and NICU settings.